Misfit strain induced out-of-interface prismatic dislocation loops in axially inhomogeneous hybrid nanowires. (October 2022) - Kolesnikova, A.L.; Chernakov, A.P.; Gutkin, M.Yu.; Romanov, A.E.
Abstract: The possibility of forming the misfit-strain-induced out-of-interface prismatic dislocation loops (PDLs) in axially inhomogeneous hybrid two-phase nanowires with a transverse interface is theoretically studied. It is shown that, due to the misfit stresses caused by the contact of two crystalline materials with different lattice parameters, the PDLs of certain radii can generate at certain distances from the interface when the nanowire radius is larger than a critical value, which depends on the lattice misfit. The critical parameters of the relaxation process are calculated and discussed in detail. Graphical abstract: Highlights: Theoretical model for stress relaxation in axially hybrid two-phase nanowires. Formation of misfit-strain-induced out-of-interface prismatic dislocation loops. The loops of certain radii can generate at certain distances from the interface. Critical conditions for loop generation are determined and discussed in detail.